SAWAHLUNTO DAN PELESTARIAN MULTIKULTURAL: SEBUAH SUMBANGSIH PEMIKIRAN UNTUK WISATA TAMBANG BERBUDAYA - Zusneli Zubir (Balai Pelestarian Nilai Budaya Sumatera Barat, 2018)
Sawahlunto is a city which formed from coal mining activity was ever victorious in its time. More orless a century more, the oldest company in Sumatera Island was ever lived and sustain the Sawahluntocity and West Sumatra in generaly. To developing this paper, there are two questions that can be asked,what the cause so Sawahluto turned into a cultural tourism with mining city? and how to developmenttourism of Sawahlunto in side analysis of SWOT?After the year 2002, Sawahlunto has entered thepurna tambang. All open mining activities are inadequate, and the revenue of Kota Sawahlunto’sAPBD also has an effect because it depends on input from PT. Bukit Asam (Persero), Tbk-Mining UnitOmbilin (PT.BA-UPO). The government of Sawahlunto, under Mayor Amran Nur, strives to bring inforeign exchange for mining cities. The concept of a mining town into a cultured mining town wascreated, it will given income of this mining tour can be a mainstay of Sawahlunto in the future, thereare some things that need to be observed, especially with regard to SWOT analysis. If four things in theSWOT analysis that can be overcome, Pemko Sawahlunto will easily make the area as a touristdestination.